Induction of Ovulation with Clomiphene Citrate Versus Clomiphene with Bromocriptine in PCOS Patients with Normal Prolactin: A Comparative Study - Tripathy, Saswati (JCDR Research and Publications (P) Limited, 2013)
Introduction: Polycystic ovarian syndrome (PCOS) is the main cause of anovulatory infertility. Various combination of drugs have been tried to induce ovulation in PCOS patients with varied result. So, this study was planned to compare the effect of bromocriptine combined with Clomiphene Citrate and Clomiphene Citrate alone, in patients of polycystic ovarian syndrome with normal prolactin level. Materials & Methods: On the basis of inclusion and exclusion criteria, seventy four PCOS patients with normal prolactin level (< 20 ng/ml) and BMI between 20-30 were randomly assigned into two groups. One group (n=38) received 50 mg clomiphene citrate (CC) from day3 to day7. The other group (CC+Bcrt) was given 50 mg of clomiphene citrate from day3 to day7 along with 0.8mg of bromocriptine daily for full cycle (n=36). Both the groups were treated for 3 cycles. The outcomes were measured by the hormonal status, follicular size, ovulation rate and pregnancy outcomes. Results: The serum prolactin level was normal in both the groups before treatment. After 3 cycles the prolactin level decreased in (CC+Bcrt) group (p< 0.01). Follicular development (size >15mm) was observed in 30 patients (78.9%) in CC group and 28 patients (82.3%) in CC+Bcrt group. There was no significant change in hormonal status (LH, FSH and Estradiol) of both the groups. The rate of ovulation was 69.4% in CC group and 75.8% in CC+Bcrt group. During the treatment period, nine patients in CC group and seven patients in CC+Bcrt group became pregnant. Conclusion: There is no added benefit of bromocriptine with clomiphene citrate as compared to clomiphene alone in ovulation induction as well as pregnancy outcomes in PCOS patients with normal prolactin.